Comparison of longitudinal changes in refractive error of hyperopic children with or without refractive accommodative esotropia - Song, Ji Eun; Han, Hyo Ji; Choi, Chul Y.; Khoramnia, Ramin; Chang, Hae Ran; Han, So Young (Diagnostics, 2021)
We investigated longitudinal changes in the spherical equivalent refractive error (SE) in hyperopic children with or without refractive accommodative esotropia (AccET). A total of 456 patients met the inclusion criteria: 190 (41.7%) in the hyperopic control group and 266 (58.3%) in the AccET group. All patients received at least 3 years of follow-up after spectacle prescription. Subgroups were divided according to age when spectacles were prescribed, presence of amblyopia, or initial SE. Longitudinal changes in SE in children with hyperopia showed a gradual decrease, although SE of younger children with AccET increased over the first 4 years and then decreased thereafter. SE in eye with higher SE was tended to decrease significantly in patient with Acc ET than hyperopic control group (group × time p = 0.015). Amblyopic eyes showed a greater decreased in SE compared with non-amblyopic eyes, but it was not statistically significant (p = 0.07). SE was significantly decreased in children with more hyperopia (≥ 3 D) compared with children with less hyperopia (<3 D) (p = 0.008). Emmetropization of hyperopia was faster in hyperopic patients without AccET and could be affected by the age of the initial spectacles prescription, initial amount of SE, or presence of amblyopia.
Gesehen am 11.11.2021